2021
DOI: 10.3389/fchem.2021.679417
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Molecular Effect on the Macroscale Friction Behaviors of Graphene

Abstract: This study investigated the friction behavior of graphene in air and nitrogen atmosphere environments. The microstructural evolution caused by the variation of atmosphere environments and its effect on the friction coefficient of the graphene is explored. It is demonstrated that graphene can exhibit excellent lubricating properties both in air and nitrogen atmosphere environments. In air, a highly ordered layer-by-layer slip structure can be formed at the sliding interface. Oxygen and H2O molecules can make ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Sukanta found that a relative humidity of 45% will cause graphene to establish a transfer layer on the contact surface, H+ and OH− ions will blunt the surface of graphene, thereby reducing friction [21]. Li found that water molecules can enter graphene interlayers and passivate defects and edge dangling bonds, resulting in weakened interlayer interactions and reduced friction coefficient [22]. Allouche found that water on the surface of layered graphite adsorption terminated the active edge bonds of graphite, thereby reducing the surface energy of graphite and improving its self-lubricating performance [23].…”
Section: Introductionmentioning
confidence: 99%
“…Sukanta found that a relative humidity of 45% will cause graphene to establish a transfer layer on the contact surface, H+ and OH− ions will blunt the surface of graphene, thereby reducing friction [21]. Li found that water molecules can enter graphene interlayers and passivate defects and edge dangling bonds, resulting in weakened interlayer interactions and reduced friction coefficient [22]. Allouche found that water on the surface of layered graphite adsorption terminated the active edge bonds of graphite, thereby reducing the surface energy of graphite and improving its self-lubricating performance [23].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, material properties, such as the crystal structure [3], hardness [4,5], elastic and shear modulus [6,7], grain size [8,9], and surface energy [10,11] of the contacting materials affect the frictional behaviour. On the other hand, the operational conditions, such as the normal loads [12,13], sliding velocities [14,15], environmental conditions [16,17], temperatures [18], and lubricants [19], have a major influence on the tribological behaviour. Of particular relevance are surface coatings or modifications of the surface topographies [20], which both can contribute significantly to the friction behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional materials such as graphene have been extensively employed as antiwear coatings at microscale due to their ultrahigh in-plane mechanical strength and ultralow interlaminar shear strength. However, their excellent tribological performance is normally difficult to be directly extended at macroscale due to abundance of defects involving atomic step edges inevitably existing in the deposited coating, which are sensitive to wear depending on the experimental atmosphere. Therefore, understanding the contributions of molecules in surrounding air to the wear of graphene step edge (a typical defect) is essential to optimizing the antiwear coating at any length scale.…”
Section: Introductionmentioning
confidence: 99%